Sport and Christianity : a sign of the times in the light of faith - Lixey, Kevin, 1968- (Catholic University of America Press, 2012)
"The modern world is dominated by sport. The Olympics and the World Cup are seen by billions of television viewers from around the globe. When Pope Benedict travels to foreign countries, typically the only venues large enough to hold the crowds for a papal Mass are sports arenas, such as London's Wembley Stadium. In response to the call of popes and the Second Vatican Council to read the signs of the times, Sport and Christianity explores the connections between these two seemingly disparate phenomena. It reflects on what the fascination for sport reveals about the human person and to what degree sporting activities are compatible with, and can even advance, the church's mission. The book discusses the attitude toward sports presented in the Old and New Testaments and in the writings of the church fathers. This leads naturally to a study of Christian anthropology, the relationship between God and man, as well as the connection between the body and the soul. There is an extensive look at sports as viewed by recent popes, including Pope Pius XII -- who denounced the use of drugs in sports as early as 1955 -- as well as Pope John Paul II, and Pope Benedict XVI. The editors pose provocative questions, such as what is Christian about sport, and how can we make sport more Christian? Ideally teamwork, pursuit of a common goal, and trying for excellence are laudable, but winning at all costs or the subjugation of Sundays to football are not. Last, given that some countries send priests as chaplains to the Olympic games and some professional sports teams have chaplains, there is a section on how to give pastoral advice to those who work in the sports professions."--Publisher's description